PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 14 BANJARBARU - Halilah, Halilah; Fitri, Ridha Rohma; Wardati, Anis Ridha (ADDABANA: Jurnal Pendidikan Agama Islam, 2020)
Abstract: This research discusses "The Use of Audio Visual Media in Learning Islamic Religious Education at SMPN 14 Banjarbaru". The formulation of the problem in this research is how to use audio visual media in learning Islamic religious education at SMPN 14 Banjarbaru and what factors influence the use of audio visual media in learning Islamic religious education at SMPN 14 Banjarbaru. Based on the problem formulation, the aim of this research is to determine the use of audio-visual media in learning Islamic religious education at SMPN 14 Banjarbaru and what factors influence it. The subjects in this research were two Islamic religious education teachers at SMPN 14 Banjarbaru. The author uses observation, interview and documentation techniques in collecting data. Meanwhile, data processing techniques are carried out by data classification, editing and data interpretation. Next, it was analyzed using qualitative descriptive analysis and conclusions were drawn inductively.Based on the research results, the use of audio visual media in learning Islamic religious education at SMPN 14 Banjarbaru has gone well. This can be seen from the teachers who teach at SMPN 14 Banjarbaru not only using textbooks when teaching, but also using learning media. One of them is Islamic Religious Education material. In using audio-visual learning media, teachers at SMPN 14 Banjarbaru have criteria for choosing learning media. So that the media used is quite varied and in accordance with the material being taught, and has taken into account the advantages and disadvantages of the media used. Factors that influence the use of audio-visual media in learning Islamic Religious Education at SMPN 14 Banjarbaru are the teacher's appropriate educational background, having teaching experience and having attended education and training as a teacher. Apart from that, the time allocation is sufficient, but the facilities and infrastructure still need to be improved. Without the availability of facilities and infrastructure supported by the school, the use of audio-visual media in learning will be hampered.Keywords: Audio Visual, PAI Learning. Abstrak: Penelitian ini membahas tentang “Penggunaan Media Audio Visual dalam Pembelajaran Pendidikan Agama Islam di SMPN 14 Banjarbaru”. Rumusan masalah dalam penelitian ini adalah Bagaimana penggunaan media audio visual dalam pembelajaran pendidikan agama Islam di SMPN 14 Banjarbaru dan apa saja Faktor-faktor yang mempengaruhi penggunaan  media audio visual dalam pembelajaran pendidikan agama Islam di SMPN 14 Banjarbaru. Berdasarkan rumusan masalah tersebut, maka tujuan penelitian ini adalah untuk mengetahui penggunaan media audio visual dalam pembelajaran pendidikan agama Islam di SMPN 14 Banjarbaru dan apa saja faktor-faktor yang mempengaruhinya. Subjek dalam penelitian ini adalah dua orang guru pendidikan agama Islam di SMPN 14 Banjarbaru. Penulis menggunakan teknik observasi, wawancara dan dokumentasi dalam pengumpulan data. Sedangkan teknik pengolahan data dilakukan dengan klasifikasi data, editing, dan interpretasi data. Selanjutnya dianalisis dengan analisis deskriptif kualitatif dan ditarik simpulan secara induktif.Berdasarkan hasil penelitian, penggunaan media audio visual dalam pembelajaran pendidikan agama islam di SMPN 14 Banjarbaru sudah berjalan dengan baik. Hal itu dapat terlihat dari guru-guru yang mengajar di SMPN 14 Banjarbaru tidak hanya menggunakan buku pelajaran ketika mengajar, tetapi juga menggunakan media-media pembelajaran. Salah satunya materi Pendidikan Agama Islam. Dalam penggunaan media pembelajaran audio visual guru-guru di SMPN 14 Banjarbaru mempunyai kreteria dalam memilih media pembelajaran. Sehingga media yang digunakan cukup bervariasi dan sesuai dengan materi yang diajarkan, serta sudah mempertimbangkan kekurangan dan kelebihan media yang digunakan. Faktor yang mempengaruhi penggunaan media audio visual dalam pembelajaran Pendidikan Agama Islam di SMPN 14 Banjarbaru adalah latar belakang pendidikan guru yang sudah sesuai, mempunyai pengalaman mengajar dan telah mengikuti pendidikan dan pelatihan sebagai guru. Selain itu alokasi waktu yang sudah mencukupi, namun dari sarana dan prasarana masih perlu ditingkatkan. Tanpa ketersediaan sarana dan prasarana yang didukung oleh pihak sekolah, penggunaan media audio visual dalam pembelajaran akan terhambat. Kata Kunci: Audio Visual, Pembelajaran PAI.